Gene design, fusion technology and TEV cleavage conditions influence the purification of oxidized disulphide-rich venom peptides in Escherichia coli. Issue 1 (December 2017) - Sequeira, Ana; Turchetto, Jeremy; Saez, Natalie; Peysson, Fanny; Ramond, Laurie; Duhoo, Yoan; Blémont, Marilyne; Fernandes, Vânia; Gama, Luís; Ferreira, Luís; Guerreiro, Catarina; Gilles, Nicolas; et al.
Abstract Background Animal venoms are large, complex libraries of bioactive, disulphide-rich peptides. These peptides, and their novel biological activities, are of increasing pharmacological and therapeutic importance. However, recombinant expression of venom peptides inEscherichia coli remains difficult due to the significant number of cysteine residues requiring effective post-translational processing. There is also an urgent need to develop high-throughput recombinant protocols applicable to the production of reticulated peptides to enable efficient screening of their drug potential. Here, a comprehensive study was developed to investigate how synthetic gene design, choice of fusion tag, compartment of expression, tag removal conditions and protease recognition site affect levels of solubility of oxidized venom peptides produced inE. coli . Results The data revealed that expression of venom peptides imposes significant pressure on cysteine codon selection. DsbC was the best fusion tag for venom peptide expression, in particular when the fusion was directed to the bacterial periplasm. While the redox activity of DsbC was not essential to maximize expression of recombinant fusion proteins, redox activity did lead to higher levels of correctly folded target peptides. With the exception of proline, the canonical TEV protease recognition site tolerated all other residues at its C-terminus, confirming that no non-native residues, which might affect activity, need to be incorporated at the N-terminus of recombinant peptides for tag removal. Conclusions This study reveals thatE. coli is a convenient heterologous host for the expression of soluble and functional venom peptides. Using the optimal construct design, a large and diverse range of animal venom peptides were produced in the µM scale. These results open up new possibilities for the high-throughput production of recombinant disulphide-rich peptides inE. coli .